Enhancing Small-Business Ecosystems Through Local Currency Designs in South Korea: A Choice Experiment Approach - Myoungjin Oh; Geunyoung Lee; Donghyun Lee; Joongha Ahn; Jungwoo Shin (Systems)
Local governments have introduced local currency systems to stimulate regional economies by encouraging local spending and preventing financial outflows. Since the success of a local currency depends on residents’ active participation, understanding consumer preferences is essential for designing effective systems. This study used a choice experiment and stated preference data to identify the features that most influence local currency adoption. Using the conditional logit model, the analysis revealed that purchase limits, merchant coverage, number of service businesses, local infrastructure, and incentives significantly impact users’ willingness to participate. The scenario analysis further highlighted the necessity of regional differentiation in currency platforms. By adopting an urban analytics approach, these results offer evidence-based insights for policymakers aiming to establish robust, spatially differentiated local currency platforms that bolster regional economic vitality across diverse urban contexts.